Ethernet bridging architecture. - Parsons, Glenn (IEEE Communications magazine)
A review of the guiding principles of the IEEE 802 architecture is presented followed by the origin and goals of the ITU-T functional architecture. The applicability of these architectures to Ethernet bridging standards is shown, specifically, how these architectures enabled 802.1Q to evolve from the enterprise to the carrier. Further, the application of ITU-T modeling to Ethernet bridging enabled simplified management for operators but also has exposed the limitations of using only a connection-oriented model.